Lead I R‐wave amplitude to distinguish ventricular arrhythmias with lead V3 transition originating from the left versus right ventricular outflow tract. Issue 1 (10th December 2020) - Wang, Jue; Miao, Chenglong; Yang, Guangmin; Xu, Lu; Xing, Ru; Jia, Yan; Zhang, Ruining; Wang, Yanwei; Huang, Liu; Liu, Suyun
Abstract: Background: The electrophysiology algorithm for localizing left or right origins of outflow tract ventricular arrhythmias (OT‐VAs) with lead V3 transition still needs further investigation in clinical practice. Hypothesis: Lead I R‐wave amplitude is effective in distinguishing the left or right origin of OT‐VAs with lead V3 transition. Methods: We measured lead I R‐wave amplitude in 82 OT‐VA patients with lead V3 transition and a positive complex in lead I who underwent successful catheter ablation from the right ventricular outflow tract (RVOT) and left ventricular outflow tract (LVOT). The optimal R‐wave threshold was identified, compared with the V2 S/V3 R index, transitional zone (TZ) index, and V2 transition ratio, and validated in a prospective cohort study. Results: Lead I R‐wave amplitude for LVOT origins was significantly higher than that for RVOT origins (0.55 ± 0.13 vs. 0.32 ± 0.15 mV; p < .001). The area under the curve (AUC) for lead I R‐wave amplitude as assessed by receiver operating characteristic (ROC) analysis was 0.926, with a cutoff value of ≥0.45 predicting LVOT origin with 92.9% sensitivity and 88.2% specificity, superior to the V2 S/V3 R index, TZ index, and V2 transition ratio. VAs in the LVOT group mainly originated from the right coronary cusp (RCC) and left and right coronary cusp junction (L‐RCC). In the prospective study, lead I R‐wave amplitude identified the LVOT origin with 92.3% accuracy. Conclusion: Lead I R‐wave amplitude provides a useful and simple criterion to identify RCC or L‐RCC origin in OT‐VAs with lead V3 transition.